High-quality DNA extraction for Desmodium gangeticum: A medicinal shrub of Shivalik Himalayas - Shiwani Singh; Maneesh S. Bhandari; Neeraj Dwivedi (Journal of Medicinal Plants for Economic Development)
Background: Desmodium gangeticum, a crucial medicinal shrub from the Himalayan Shivalik region, is an economically important species globally. It contains a vast range of secondary metabolites, majorly polyphenols, that interfere with high-quality deoxyribonucleic acid (DNA) extraction by binding their oxidised form to DNA covalently and rendering it unusable for molecular research.